Engagement of employees of generation Y – theoretical issues and research experience - Kopertyńska, Maria Wanda; Kmiotek, Krystyna (Wydawnictwo Uniwersytetu Ekonomicznego we Wrocławiu, 2015)
In the conditions of a turbulent environment, of the fast development of technology, and of the increasing role of innovativeness in the success of enterprises, the mutual expectations of employees and employers have been changing. Employers expect from employees not only high motivation, but as great engagement as possible in the completion of business objectives. Employees have been changing as well. The labour market is being entered by Generation Y, who as employees present a different approach to work and duties. This forces employers to focus greater attention and use a different approach in selecting motivational instruments and building engagement. The purpose of this article is to identify the problems related to building the engagement of employees of the youngest generation. The authors point out the specific qualities of Generation Y based on literature, mainly from western countries, and then, based on their own research involving 382 managers and 1505 Generation Y employees from 16 Polish enterprises, indicate the distinguishing characteristics of the youngest employees. The research shows that according to the self-evaluation of Generation Y employees and the manager’s opinion the level of engagement of the youngest employees is not significantly different from their older co-workers, but the research confirms the dissimilarity of Generation Y interviewee’s approach to work and tasks. It brings to their supervisors as well as human resources departments a new task to search for a new organizational solutions and ways of improving work conditions to support the engagement development of young employees.
Argumenta Oeconomica, 2015, Nr 2 (35), s. 185-201
Keywords: generation Y; motivating; motivation; engagement; human resources management; managers